Translating genomic medicine to the clinic: challenges and opportunities - Zhang, Huan; Pfister, Stefan (Genome medicine, 2019)
Genomic medicine has considerable potential to provide novel diagnostic and therapeutic solutions for patients who have molecularly complex diseases and who are not responding to existing therapies. To bridge the gap between genomic medicine and clinical practice, integration of various data types, resources, and joint international initiatives will be required.
Gesehen am 24.07.2019